Освітні зв'язки кафедр педагогіки закладів вищої педагогічної освіти - Золотухіна, Світлана; Башкір, Ольга (Національний технічний університет "Харківський політехнічний інститут", 2019)
У публікації досліджено освітні зв’язки кафедр педагогіки закладів вищої педагогічної освіти України другої половини XX ст. для вдосконалення змісту та практики підготовки майбутніх учителів; розглянуто активну співпрацю кафедр педагогіки із закладами загальної середньої та вищої освіти на базах опорних шкіл і кафедр, пришкільних кабінетів педагогіки, педагогічних класів, клубів, навчально-дослідних лабораторій, експериментальних майданчиків; розкрито характер взаємозв’язку кафедр із науковими установами, інститутами підвищення кваліфікації вчителів, їхніми керівниками, викладачами та співробітниками.

The educational contacts of departments of pedagogy of institutions of higher pedagogical education of Ukraine of the second half of the twentieth century are studied. The active cooperation of the departments of pedagogy with the institutions of general secondary and higher education on the bases of the basic schools and departments, school offices of pedagogy, pedagogical classes, clubs, educational research laboratories, and experimental sites is considered. The specifics of the relationship between departments and scientific institutions, institutes of teacher professional development, their heads, teachers and employees are revealed.
Educational relations of departments of pedagogy of institutions of higher pedagogical education
Keywords: історія; взаємозв’язок; history; interconnection